Sensitivity of Scale Points in Switching of Customers in Terms of Level of Impulsiveness - Santanu Choudhury, Dibyojyoti Bhattacharjee (Mathematical Statistician and Engineering Applications, 2022)
Impulsive purchases are often identified in response to incentives to buy. This move focuses on the situational factors which lead to impulse buying without regard to individual characteristics. Most of the studies focused on the impact of store environment on impulsive buying. Thus, the objective of this study is to find the most compatible scale points for the impulsive buying behavior scale by Rook and Fisher for consumers in the level of impulsiveness. From study, it is concluded that the 9-point scale is the most sensitive scale compared to other scale points in terms of the switching nature of the consumers.